Healthy House as Indicator to Realize Healthy City and its Relationship with the Role of Community in Medan City - Lita Sri Andayani; Juliandi Harahap (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
A healthy city connotes a city that is clean, comfortable, safe and healthy for inhabitants, which is achieved  through  the  implementation  of  the  arrangements  and  agreed  activities  between communities and local government units. Healthy house is one indicator of a healthy city. A healthy house meets the health requirements as measured by three parameters: components of house, sanitation facilities and the behavior of occupants. This study aimed to analyze if the houses in Medan qualify for the attainment of a healthy city, determine the knowledge of community in terms of healthy house, healthy city and the role of community, and to find out if there is a significant relationship between the role of community and having a healthy house. The study design used is survey with quantitative and qualitative approaches. Research sites were the 21 districts in the city of Medan wherein 400 respondents were selected through proportional random sampling. Data were analyzed quantitatively and qualitatively. The results showed that in the city of Medan, only 30% of houses were healthy and 70% were not. 63.0% of the respondents have good knowledge about healthy house  and  57.8% have good  knowledge about healthy city. Furthermore, the community perceived to have played a good role as much as 75.5% in the effort to realize a healthy home/city. The community’s role has a positive and significant effect on healthy house in efforts to achieve a healthy city in Medan (p = 0.04). It is recommended that the government of Medan City draw up a program of healthy house and healthy city and involve related stakeholders, increase  community  participation from  the  beginning of  planning  stage  in  order  to  increase community involvement in the implementation of development and formation of Healthy City Forum.